Regeneracion y crecimiento de la caoba (Swietenia macrophylla King) en selvas de Quintana Roo - Snook, Laura K. (2000)
To determine the regeneration dynamics and growth rate of mahogany in the natural tropical forests of Quintana Roo, oral histories were used to find essentially even-aged stands that had become established naturally between 2 and 75 years ago, after a hurricane, forest fires, or mechanical distrubance (logyards) had occured. Trees in these stands were sampled using transects and sample plots, and differentiated into residual trees that had become established subsequently. New individuals of mahogany became established at an average density of 18 per ha after fires and 6 per ha after hurricane. This pattern indicates that mahoganies become established more successfully on clearings than in gaps, which are densely populated with saplings and seedlings of other species. The average diameters of post-disturbance mahoganies in stands of different ages revealed that mahogany trees grow to 26 cm DBH in 45 years and 37 cm DBH in 75 years. Extrapolating from the last periodic annual increment (0.38 cm year-1), it was calculated that a mahogany tree requires over 120 years to reach the current commercial diameter of 55 cm, although the fastest growing trees may reach this size in 82 years. To ensure the sustainability of mahogany timber harvests from the forests of Quintana Roo, it would be appropriate to reevaluate the current cutting cycle in light of the calculated growth rates, and to try to duplicate the conditions that have favored natural regeneration of mahogany in these forests.